Valorization of Wastes from Power Plant, Steel-Making and Palm Oil Industries as Partial Sand Substitute in Concrete - Ong, Seng Kuan; Mo, Kim Hung; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Ling, Tung Chai (Springer Netherlands, 2018)
For long, the growing amount of solid wastes from various industries has created disposal issues and caused serious environmental concerns. Increased efforts have been carried out to recycle and valorize the industrial wastes into use as concrete-making materials. Due to the current growth of construction industries around the world, natural sand is depleting rapidly and as such raises environmental issues such as erosion, flooding and disruption of eco-system. Sourcing alternative materials to replace sand in concrete would be ideal in promoting sustainability for the environment as well as the construction industry. Therefore, this research explores the potential of utilizing local industrial wastes such as palm oil clinker from the palm oil industry, coal bottom ash from power plant as well as steel slag from the steel-making industry as partial sand substitute in concrete. Based on the tested concrete properties such as compressive strength, splitting tensile strength, sorptivity and shrinkage, it was found that incorporation of these industrial wastes at 50% replacement level generally did not cause substantial negative impact to the resulting concrete. In terms of the optimum concrete performance, it is suggested to incorporate these industrial wastes at 30% replacement level.